2011
DOI: 10.1093/esr/jcr008
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national Variation in the Influence of Employment Hours on Child Care Time

Abstract: Parental time investments in children are essential inputs in children's present and future well-being. The ability of parents to make choices about child care time that are free from money and time constraints varies considerably, however, by employment status and country. We use nationally representative time diary data from nine countries with different gendered working time regimes to investigate how employment hours influence child care time, and whether parents in countries with high maternal employment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 44 publications
1
94
1
1
Order By: Relevance
“…As stated earlier, a family which has one full-time worker and one part-time worker has been characterised in work-family literature as a 1.5 worker family (Sayer and Gornick, 2012). To reiterate, Michala is a full-time care professional.…”
Section: This Case Considers the Ways In Which Michala (A Full-time Wmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated earlier, a family which has one full-time worker and one part-time worker has been characterised in work-family literature as a 1.5 worker family (Sayer and Gornick, 2012). To reiterate, Michala is a full-time care professional.…”
Section: This Case Considers the Ways In Which Michala (A Full-time Wmentioning
confidence: 99%
“…Consequently, this trend of part-time working hours has a knock-on effect that women will also tend to earn less income through paid-work. Working practices within the UK have been termed 1.5 worker families (Prince Cooke, 2011;Sayer and Gornick, 2012) which refer to a family with one part-time worker and one full-time worker, with typically the mother taking on the part-time role. Despite gender mainstreaming commitments within EU policy directives, UK policy compares poorly by reinforcing traditional gendered caring and working constructs of mother as primary carer and father as breadwinner worker (Sigle-Rushton and Kenney, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that women who are currently on leave or not employed on average perform more and their partners less unpaid work compared to women who work part-time or full-time (e.g., Gershuny et al 2005, Brines 1994, Sayer and Gornick 2012, Craig and Mullan 2011. A few analyses of domestic work time differentiated between short-term and long-term unemployment (Brines 1994, Burda andHamermesh 2009) or considered women's full-time work experience (Cunningham 2007) and generally lend some support to the importance of past labour market experiences.…”
Section: Previous Research On Parental Leave and Domestic Work After mentioning
confidence: 99%
“…In contrast, because of the persisting view of good fathering in terms of good breadwinning, there is little to no societal ambivalence towards new fathers' employment. This is reflected in the relatively small variability in fathers' working patterns (Sayer & Gornick, 2012), which leaves less room for fathers' identities in guiding their behaviors.…”
Section: Work Identities and Involvement In Childcarementioning
confidence: 99%